2018
DOI: 10.1038/s41396-018-0095-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spatial organization on a novel auxotrophic interaction among soil microbes

Abstract: A key prerequisite to achieve a deeper understanding of microbial communities and to engineer synthetic ones is to identify the individual metabolic interactions among key species and how these interactions are affected by different environmental factors. Deciphering the physiological basis of species–species and species–environment interactions in spatially organized environments requires reductionist approaches using ecologically and functionally relevant species. To this end, we focus here on a defined syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 88 publications
(112 reference statements)
0
52
0
Order By: Relevance
“…irregularis (Tisserant et al ., ; Lin et al ., ; Wewer et al ., ). Loss of thiamine biosynthesis has been observed in several fungi (Jiang et al ., ), and at least one of the biosynthetic enzymes is enzymatically costly, so loss of the pathway may be advantageous in certain environments. Interestingly, Serendipita indica , a thiamine auxotroph and endophyte of plants, can use thiamine provided by either plants or bacteria (Jiang et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…irregularis (Tisserant et al ., ; Lin et al ., ; Wewer et al ., ). Loss of thiamine biosynthesis has been observed in several fungi (Jiang et al ., ), and at least one of the biosynthetic enzymes is enzymatically costly, so loss of the pathway may be advantageous in certain environments. Interestingly, Serendipita indica , a thiamine auxotroph and endophyte of plants, can use thiamine provided by either plants or bacteria (Jiang et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Computational and in vivo studies have shown that spatial structure of microbial communities is a determining factor for cooperation and can drive community dynamics 16,52,53 . Co-culture experiments involving Bacillus subtilis and the endophytic fungus Serendipita indica revealed that thiamine (vitamin B 1 ) is a key nutrient for the B 1 auxotroph S. indica .…”
Section: Network Dynamics and Cross-feedingmentioning
confidence: 99%
“…Indeed, multiple studies have shown how syntrophic cross-feeding interactions, based on the reciprocal exchange of amino acids, lead to stable coexistence 2,7 . Auxotrophies are therefore likely to play a prominent role in determining the composition and stability of microbial communities [8][9][10] .…”
mentioning
confidence: 99%